Change your world : how anyone, anywhere can make a difference - Maxwell, John C. (Nashville, Tennessee : HarperCollins Leadership, 2021)
Two of today's most respected world-changers, leadership expert John C. Maxwell and global development leader Rob Hoskins, share their real-world experiences helping to transform millions of lives, communities, and businesses around the world to show people how to be the change the world needs and help others do the same.
Keywords: LEADERSHIP